2024
DOI: 10.2174/1566524023666230602162949
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Resveratrol in Aging and Senescence: A Focus on Molecular Mechanisms

Zeynab Kohandel,
Majid Darrudi,
Kobra Naseri
et al.

Abstract: Resveratrol (Res), a polyphenol found in red wine, has been shown to decelerate aging, the progressive loss of physiological integrity and cellular senescence, characterized by the inability to progress through the cell cycle. No successful clinical trials have yet to be completed in humans on dose limitations. Yet, the potent anti-aging and anti-senescence efficacy of Res has been documented in several in vivo animal models. In this review, we highlight the molecular mechanisms of Res efficacy in anti-aging d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Our results demonstrated that dasatinib with resveratrol, a stilbene, and dasatinib with ellagic acid, a dilactone of hexahydroxydiphenic acid, have potential as senolytics. Resveratrol can induce growth inhibition and apoptosis in tumor cell lines at 70–150 μM [ 34 , 35 ] and exert beneficial effects in aging models by its pharmacological activation of SIRT1 [ 36 ]. However, a senolytic activity screening demonstrated a negative result [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrated that dasatinib with resveratrol, a stilbene, and dasatinib with ellagic acid, a dilactone of hexahydroxydiphenic acid, have potential as senolytics. Resveratrol can induce growth inhibition and apoptosis in tumor cell lines at 70–150 μM [ 34 , 35 ] and exert beneficial effects in aging models by its pharmacological activation of SIRT1 [ 36 ]. However, a senolytic activity screening demonstrated a negative result [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…As it is known, most polyphenols can cross the blood-brain barrier; therefore, they are widely utilized in the treatment of various neurodegenerative diseases (ND). Resveratrol is a polyphenol and, at the same time, hydroxy-2 stilbene; as such, it is a promising neuroprotective agent against neurodegenerative disorders such as Alzheimer's disease (AD) besides its significant antioxidative behavior [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol, a stilbene derivative, is a natural nutrient in grapes, which possesses many biological characteristics, such as anti-inflammatory, neuroprotective, anti-cancer, anti-oxidative, and anti-diabetic effects [ 11 , 12 , 13 ]. In recent years, the anti-aging potential of resveratrol has been one of the most eye-catching biological activities [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Resveratrol is a potential candidate as an anti-aging agent, which can exert its anti-aging and health benefits via anti-oxidative, calorie-restrictive, and anti-inflammatory effects through activating the nuclear factor erythroid 2-related factor 2 (Nrf2), sirtuin 1 (Sirt1), and AMP-activated protein kinase (AMPK) signaling pathways.…”
Section: Introductionmentioning
confidence: 99%